Механизм безопасности клепального пресса - Чемерис, Е. И.; Chemeris, E.; Чемерис, Є. І. (КНТУ, 2013)
В данной работе предлагается механизм безопасности клепального пресса и анализируются особенности его работы. В даній роботі пропонується механізм безпеки клепального пресу та аналізуються особливості його роботи. The objective of the article is the description of the construction of the mechanism of riveting press and research of its operation. As a result of the research done by the author on the work of operators on riveting the details on riveting press, technical recommendations to provide safety of the work was suggested. The suggested mechanism provides adaptive control of the slide-block strain according to the changing operating mode. The advantage of the recommendation is reliable response of the safety mechanism which avoids injuring an operator while practical influence the process of work.
Механізм безпеки клепального пресу
The mechanism of safety of riveting press
Keywords: операции склепывания; операторы-штамповщики; устройства безопасности; операції склепування; оператори-штампувальники; пристрої безпеки; riveting operations; operators of stampers; safety devices